2009
DOI: 10.1093/scan/nsp019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions of the serotonin transporter to social learning of fear and economic decision making

Abstract: Serotonin (5-HT) modulates emotional and cognitive functions such as fear conditioning (FC) and decision making. This study investigated the effects of a functional polymorphism in the regulatory region (5-HTTLPR) of the human 5-HT transporter (5-HTT) gene on observational FC, risk taking and susceptibility to framing in decision making under uncertainty, as well as multidimensional anxiety and autonomic control of the heart in healthy volunteers. The present results indicate that in comparison to the homozygo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 66 publications
12
123
0
Order By: Relevance
“…More neurons mean a stronger connection and may be associated with a greater capacity to detect the emotional context of an environment. Short allele carriers express greater sympathetic reactivity when observing another person receiving a shock (Crişan et al 2009), suggesting a possible link to a greater capacity for empathy. In another study, it was found that seeing a favourite person led to significantly higher amygdala activity in short allele carriers suggesting a higher reward value of positive interpersonal experience (Matsunagaa et al 2010).…”
Section: Serotonin Transporter Imaging and Post-mortem Studies Of Suimentioning
confidence: 99%
“…More neurons mean a stronger connection and may be associated with a greater capacity to detect the emotional context of an environment. Short allele carriers express greater sympathetic reactivity when observing another person receiving a shock (Crişan et al 2009), suggesting a possible link to a greater capacity for empathy. In another study, it was found that seeing a favourite person led to significantly higher amygdala activity in short allele carriers suggesting a higher reward value of positive interpersonal experience (Matsunagaa et al 2010).…”
Section: Serotonin Transporter Imaging and Post-mortem Studies Of Suimentioning
confidence: 99%
“…HRV is positively related to serotonin turnover (DePetrillo et al, 1999). Individuals carrying s allele of serotonin transporter gene showed reduced HRV compared to l-homozygotes (Crişan et al, 2009). Lower levels of serotonin induced by tryptophan depletion were associated with reduced HRV in remitted depressed patients (Booij et al, 2005).…”
Section: The Neurovisceral Integration Model Of Anxietymentioning
confidence: 91%
“…High trait anxiety was associated with autonomic dysreguation indexed by reduced HRV . Thus, reduced HRV may play a critical role in the development of anxiety disorders and can be considered as an important endophenotype of anxiety (Friedman, 2007;Crişan et al, 2009). In a recent review of the literature, Friedman (2007) provided a number of studies that linked reduced HRV with a variety of anxiety disorders over the past 15 years and provided the summary of the Neurovisceral Integration model of anxiety.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…Homberg & Lesch [11], as well as Falk et al [16], propose that the short allele may therefore result in greater social conformity. Further evidence that 5HTTLPR influences social learning or imitation per se is provided by an association between the short allele and increased observational fear conditioning [17], as well as anatomical differences in the mirror neuron system [18] and activational differences upon viewing emotional expressions [18] and performing a joint action task [19].…”
Section: Introductionmentioning
confidence: 99%